Developing C.O.C (Congklak, Onet & Crossword Puzzle) Game to Motivate Students in Enriching English’ Vocabulary (RETAIN, 2018)
Abstract Vocabulary is one of the important factors in learning foreign language such as English. Based on widely observation, most of Indonesian students are having difficulty in understanding English vocabulary which leads to the difficulty to acquire foreign language. One way to solve the problem is by using a medium in the form of a game. A game called C.O.C is developed under R&D design into an effective medium. R&D design is a research design that used in creating a new product and evaluating the product through some experiments. This method included some stages such as material and expert validation, also field evaluation. The field evaluation is held at one of Junior High Schools in Surabaya. The seventh grade of this school become the participant in the research. The aim is to find out either the game is work or not and could it motivates student in enriching English’ vocabulary. Based on this research, it is showed that the use of C.O.C game could motivate students in enriching vocabulary. Key words : Vocabulary, Motivation, Medium, R&D Abstrak Kosa kata adalah salah satu faktor yang penting dalam belajar bahasa asing seperti Bahasa Inggris. Berdasarkan hasil obervasi secara luas, mayoritas siswa di Indonesia memiliki kesulitan dalam memahami kosa kata yang menghambat mereka dalam menguasai bahasa asing. Salah satu cara untuk menghadapi masalah ini adalah dengan menggunakan media berbentuk permainan. Sebuah permainan dengan nama C.O.C telah dikembangkan menjadi media yang efektif dengan menggunakan rancangan penelitian R&D. R&D adalah rancangan penelitian yang digunakan untuk menciptakan produk baru dan mengevaluasi produk tersebut melalui beberapa percobaan. Rancangan penelitian ini mencantumkan beberapa tahapan seperti validasi materi dan media, serta evaluasi lapangan. Evaluasi lapangan di laksanakan di salah satu Sekolah Menengah Pertama di Surabaya. Kelas 7 dari sekolah ini di pilih sebagai peserta dalam penelitian. Tujuannya untuk mengetahui apakah permainan yang telah dikembangkan dapat di jalankan atau tidak dan apakah dapat memotivasi siswa dalam memperkaya kosa kata bahasa Inggris mereka. Berdasarkan hasil penelitian, penggunaan permainan C.O.C dapat memotivasi siswa dalam memperkaya kosa kata Bahasa Inggris. Kata Kunci: Kosa Kata, Motivation, Media, R&D.